Наверх

Упростите выражение 2sin^2a ----------- tg2a*tga

Упростите выражение 2sin^2a ----------- tg2a*tga
  • Поделиться
1 ответ 997 07 Сен 2016 1 рейтинг
Войдите, чтобы оставить свой ответ
Войти Зарегистрироваться
КсенияВолохова Поделится
  • Поделиться
Tg2a=2tga/(1-tga) 2sina 2 sina *(1-tga) 2sina (1-sina/cosa) ------------------------ = ---------------------- = ---------------------------- = 2tga*tga/(1-tga) 2 tga 2sina/cosa =cosa(cosa-sina)/cosa=(cosa-sina)=cos2a
Не нашли ответ на свой вопрос? Попробуйте спросить